Is globalization good for your health? - Dollar, David (2001)
Interjects four points into the debate about globalization and health. Deals with globalization in the sense of increased integration of different economies and societies as a result of greater flows of goods, capital people and ideas. Notes that economic integration is a powerful force for raising the incomes of poor countries. Suggests that there is no tendency for income inequality to increase in countries that open up. Posits that economic integration can have adverse health effects as well e. g. the transmission of AIDS through migration and travel. States that with economic integration, international architecture can be improved so that it is more beneficial to poor countries.